Charlotte's Web - White, E. B. 1899- (Elwyn Brooks) (Chagrin Falls, Ohio : Findaway World, 2006)
Wilbur the pig is desolate when he discovers he is destined to be the farmer's Christmas dinner, until his spider friend Charlotte comes up with a plan to save him.